13C nuclear magnetic resonance spectroscopy to check 1, 3-random, 2-random pattern of fatty acid distribution in olive oil triacylglycerols. Issue 2 (2005) - Vlahov Vlahov, Giovanna Giovanna
Abstract : The fatty acid distribution between the 1, 3- and 2-positions of triglycerides was determined in the olive oil set sampled in the Marche region, by using the 13 C NMR method which applies the DEPT pulse sequence. The results confirmed that the oleic and linoleic acids were not randomly distributed at the 2-position of triacylglycerols but were lower for oleic acid and higher for linoleic acid compared to the theoretical values expected for a random distribution. Moreover, the unsaturated acids deviated from the 2-random distribution at different extents according to the acid concentration of triglyceride. The 13 C NMR results, they were obtained for three olive oil samples characterized by high, medium and low oleic acid at 2-position (Ofound ) corresponding to a low, medium, high deviation rate from the 2-random pattern, were compared to those calculated by the computer program based on the 1, 3-random−2-random distribution of fatty acids in the triglycerides. The molar concentrations of the triglyceride species LLL and OLL were calculated from the molar concentrations of oleic and linoleic acids at the 2- and 1, 3-positions obtained by using 13 C NMR and the computer method. The LLL and OLL triglycerides determined by the computer method were found to be markedly higher in the "high Ofound " oil as compared to NMR. No differences were detected between the two methods for both triglyceride species in the "low Ofound " oil.